Quality of Educational Service at the Faculty of Social Sciences and Humanities of a Public University - Lidia Luz Cruz Neyra (Universidade Estadual do Ceará, 2021)
The quality of the educational service is one of the factors that is present as the objective of every university institution and, therefore, the quality of training of professionals in Peru, both in its face-to-face and remote modality. The objective of the research was to determine the association of expectation and perception of the quality of educational service provided by the National University of Education. The selected exhibition consisted of 189 students from the Faculty of Social Sciences and Humanities. They responded to the survey based on the SERVQUAL model that measures the expectation of students of a university of excellence and the perception of educational service that is offered by the institution. The association between the two variables was evaluated through Spearman's Rho correlation. The results demonstrate a weak association of student expectation and perception variables at a significance level of 0.05. Likewise, these results are extended to the security dimension, in contrast to the other dimensions such as tangibility, responsiveness, empathy and reliability. This means that the gaps (P-E) that are the differences between perception (P) and Expectations (E) suggest that improvement plans must be implemented to obtain the quality of educational service that students demand.